(untitled) (Medico Legal Update, 2020)
Dengue is one of the most common mosquito borne diseases in India and it is most prevalent condition in the community. The number of cases of dengue goes up high during monsoon season as the mosquito breed in stagnant water and in warm and humid weather. The study topic was “Effects of video assisted teaching on prevention and management of dengue among mothers in selected rural community, Kanchipuram District, Tamil Nadu, India”. The objectives of the study were to assess the pre and post-test knowledge of mothers regarding prevention and management of dengue, to assess the effectiveness on video assisted teaching among the mothers in the rural community and to find out the association between pre-test knowledge scores regarding prevention and management of dengue with selected demographic variable. Quantitative research approach was used for this study. Quasi-experimental, one group pre-test post-test design was used for this study. The sample consists of 194 mothers. Self structure questionnaire was used to assess the effect on video assisted teaching on prevention and management of dengue. The data collection period was one week. The data was collected in 194 mothers in the age group between 20 to 60 years in pooncheri rural community. The samples are selected by using simple random sampling technique. The data was analyzed and tabulated. The results shows pre-test knowledge scores on prevention and management on dengue was 51% (98) had moderate knowledge, 43% (84) had inadequate, 6%(12) had adequate knowledge. Post-test knowledge scores after video assisted teaching on prevention and management on dengue was 9%(18) had moderate knowledge and 91% (176) had adequate knowledge. Study shows that there was significant association between pre-test and post-test knowledge of mothers with T Value of 25.76 which was statistically significant at p<0.05 level. The post-test knowledge score was greater than the pre-test knowledge score (pre-test-13.70 < post-test-21.57).